Effect of Nitrosative Stress on the S-Nitroso-Proteome of Paracoccidioides brasiliensis - Navarro, Marina V.; Chaves, Alison F. A.; Castilho, Daniele G.; Casula, Isis; Calado, Juliana C. P.; Conceição, Palloma M.; Iwai, Leo K.; de Castro, Beatriz F.; Batista, Wagner L. (Frontiers in Microbiology, 2020)
The fungi Paracoccidioides brasiliensis and Paracoccidioides lutzii are the causative agents of paracoccidioidomycosis (PCM), a systemic mycosis endemic to Latin America. This fungus is considered a facultative intracellular pathogen that is able to survive and replicate inside macrophages. The survival of the fungus during infection depends on its adaptability to various conditions, such as nitrosative/oxidative stress produced by the host immune cells, particularly alveolar macrophages. Currently, there is little knowledge about the Paracoccidioides spp. signaling pathways involved in the fungus evasion mechanism of the host defense response. However, it is known that some of these pathways are triggered by reactive oxygen species and reactive nitrogen species (ROS/RNS) produced by host cells. Considering that the effects of NO (nitric oxide) on pathogens are concentration dependent, such effects could alter the redox state of cysteine residues by influencing (activating or inhibiting) a variety of protein functions, notably S-nitrosylation, a highly important NO-dependent posttranslational modification that regulates cellular functions and signaling pathways. It has been demonstrated by our group that P. brasiliensis yeast cells proliferate when exposed to low NO concentrations. Thus, this work investigated the modulation profile of S-nitrosylated proteins of P. brasiliensis, as well as identifying S-nitrosylation sites after treatment with RNS. Through mass spectrometry analysis (LC-MS/MS) and label-free quantification, it was possible to identify 474 proteins in the S-nitrosylated proteome study. With this approach, we observed that proteins treated with NO at low concentrations presented a proliferative response pattern, with several proteins involved in cellular cycle regulation and growth being activated. These proteins appear to play important roles in fungal virulence. On the other hand, fungus stimulated by high NO concentrations exhibited a survival response pattern. Among these S-nitrosylated proteins we identified several potential molecular targets for fungal disease therapy, including cell wall integrity pathway, amino acid and folic acid metabolisms. In addition, we detected that the transnitrosylation/denitrosylation redox signaling are preserved in this fungus. Finally, this work may help to uncover the beneficial and antifungal properties of NO in the P. brasiliensis and point to useful targets for the development of antifungal drugs.